ANALISIS PENGARUH MARGIN BANK SYARIAH, PREFERENSI KONSUMEN DAN PENDAPATAN TERHADAP KEPUTUSAN NASABAH MENGAMBIL KPR SYARIAH - Azimah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to analyze the effect of bank margins, customer preferences and income on customer decisions to take Sharia mortgages. the term Ordinary Least Squares (OLS) regression. The difference is that in logistic regression, the researcher predicts the dependent variable on a dichotomous scale. The dichotomous scale in question is a nominal data scale with two categories, for example: Yes and No, Good and Bad or High and Low. Based on the results of logistic regression analysis, it was found that the characteristics of Islamic mortgages, income factors, consumer preference factors and the influence of Islamic bank margins had a significant effect on customer decisions in taking Sharia mortgages. While the knowledge factor does not have a significant effect. Based on the results of the logistic regression coefficients, the characteristic factor of Islamic mortgages is the dominant factor in customer decisions to choose Islamic mortgages because they have the largest beta value.